Protecting the viability of encapsulated Lactobacillus rhamnosus LGG using chocolate as a carrier - Hossain, Md Nur; Ranadheera, Chaminda Senaka; Fang, Zhongxiang; Hutchinson, Graham; Ajlouni, Said (Emirates Journal of Food and Agriculture, 2021)
The novel probiotic encapsulation approaches in snacks have not been thoroughly investigated. This study examined the viability of encapsulated Lactobacillus rhamnosus LGG using chocolate as a carrier. Various encapsulants, including cocoa powder, Na-alginate, fructooligosaccharides, whey protein concentrate, hi-maize starch and skim milk powder were tested using a freeze-drying technique. The encapsulation efficiency of L. rhamnosus reached 91.82% using cocoa powder and Na-alginate formulations. The encapsulated probiotic survived at thermal exposure maintaining more than 9 logs at 60°C. Chocolate was proven as a good carrier for encapsulated probiotic maintained viability above the therapeutic level (107 log) up to 180 and 120 days stored at 4°C and 25°C, respectively. Additionally, encapsulated L. rhamnosus in chocolate showed higher survival number (8.47 log cfu/g) at the end of gastrointestinal digestion. Hence, cocoa powder with Na-alginate as an encapsulation agent has potential applications in the development of healthy probiotic chocolate.